2021
DOI: 10.1556/038.55.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control Agents in the Management of Different Initial Population Densities of Meloidogyne javanica in Tomato

Abstract: The efficacy of single and combined application of Trichoderma harzianum and Pseudomonas fluorescens (CHA0) in the controlling of Meloidogyne javanica on tomato plants was evaluated under green house conditions. Seeds of the susceptible tomato cv. Early-Urbana were sown in clean plastic pots containing 1.5 kg steam sterilized soil. Four weeks after planting, the soil of each pot was infested with a suspension of 20 ml/kg soil of T. harzianum (106 spores/ ml) and a suspension of 15 ml/kg soil of P. fluorescens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Bacillus velezensis GF267 reduced the intensity of tomato bacterial spots and increased the chlorophyll content in plants as reported by Mates et al (2019). Various strains of Pseudomonas fluorescens have also been shown to be effective biocontrol agents against multiple plant diseases (Yendyo et al, 2017;Kulimushi et al, 2021;Mosahaneh et al, 2021). As observed in the current study, the combination of these two isolates was more effective in controlling wilt as compared to the treatments containing these isolates alone.…”
Section: Discussionsupporting
confidence: 74%
“…Bacillus velezensis GF267 reduced the intensity of tomato bacterial spots and increased the chlorophyll content in plants as reported by Mates et al (2019). Various strains of Pseudomonas fluorescens have also been shown to be effective biocontrol agents against multiple plant diseases (Yendyo et al, 2017;Kulimushi et al, 2021;Mosahaneh et al, 2021). As observed in the current study, the combination of these two isolates was more effective in controlling wilt as compared to the treatments containing these isolates alone.…”
Section: Discussionsupporting
confidence: 74%
“…It is necessary to discover cheap, applicable, effective, and efficient solutions to overcome this problem. An effort that can be done is to develop a bionematicide formula with the active materials of antagonistic bacteria (Viljoen et al 2019;Mosahaneh et al 2021). In previous study, we found 8 bacterial isolates including 6 endophytic bacteria and 2 rhizobacteria.…”
Section: Introductionmentioning
confidence: 97%
“…(Mosahaneh et al 2021) and bacteria Pseudomonas spp. (Mosahaneh et al 2021) and Bacillus spp. (Viljoen et al 2019) against M. javanica and M. incognita, in tomato.…”
mentioning
confidence: 99%
“…Several biotic agents have been used to induce resistance in plants to nematodes, such as the yeast Pochonia chlamydosporia (Ghahremani et al 2019), the filamentous fungi Trichoderma spp. (Mosahaneh et al 2021) and bacteria Pseudomonas spp. (Mosahaneh et al 2021) and Bacillus spp.…”
mentioning
confidence: 99%